Special effects artists : a worldwide biographical dictionary of the pre-digital era with a filmography - Giesen, Rolf, 1953- (McFarland & Company, 2008)
"Alphabetized entries provide career synopses and movie credits for important special effects practitioners and inventors, spanning the early years of cinematography through the end of the mechanical age of filmmaking. Coverage ranges from pioneers through modern special effects masters working with traditional techniques. A select chronological filmography, a glossary of technical terms and numerous publicity stills are included."-- Vydavatrelská anotace
Terminologický slovník
Keywords: bibliografické slovníky; filmografie; bibliographical dictionaries; filmography; 1913-1993; 20. století; filmová výroba -- 20. století; filmové efekty -- 20. století; filmové triky -- 20. století; filmová animace -- 20. století; filmoví umělci -- 20. století; dějiny filmu -- 20. století; film production industry -- 20th century; film effects -- 20th century; film animation -- 20th century; film artists -- 20th century; history of film -- 20th century